Consistent action of two partially effective loci conferring resistance to Globodera pallida Pa2/3 across multiple nematode field populations. (8th December 2016) - Rigney, B.; Blok, V.; Griffin, D.; Dalton, E.; Milbourne, D.
Abstract : The potato cyst nematodes (PCN) Globodera rostochiensis and Globodera pallida are significant pests of potatoes worldwide. The most effective control methods are crop rotation and the deployment of resistant varieties. Complete resistance to G. rostochiensis based on a single resistance gene has successfully been integrated into many varieties. However, resistance to G. pallida has not been as successful to date, with current varieties only exhibiting partial resistance. Combining partially effective quantitative trait loci (QTLs) for resistance can increase the strength and breadth of the resistance. An additive effect on resistance has previously been demonstrated on combining two QTLs from Solanum tuberosum subsp. andigena ( GpaIV s ad g ) and Solanum vernei ( Gpa5 ). However, populations of G. pallida can be quite divergent and it was unclear whether the relative effects of the individual QTLs and the combined additive effect would be consistent across different G. pallida Pa2/3 populations. Using a mapping population segregating for both QTLs, the effect of the QTLs individually and combined was examined on four UK‐derived field populations of G. pallida pathotype Pa2/3, and the relative effects of the individual QTLs and the additive effect of the combination found to be consistent across all populations.